Nanomedicines for targeted delivery of etoposide to non-small cell lung cancer using transferrin functionalized nanoparticles. Issue 61 (4th July 2015) - Pooja, Deep; Kulhari, Hitesh; Tunki, Lakshmi; Chinde, Srinivas; Kuncha, Madhusudana; Grover, Paramjit; Rachamalla, Shyam S.; Sistla, Ramakrishna
<x xml:space="preserve">Abstract</x> Tf-conjugated solid lipid nanoparticles were designed for selectively targeting etoposide to human non-small cell lung cancer resulting in sustained drug release, improved plasma concentrations and accumulation of etoposide in targeted lung tissues.